Effect of a quality improvement package on reducing newborn mortality from 26 to 14 in a Himalayan North Indian State - Seema Sharma; Mangla Sood; Kavya Sharma; Ishaan Sood (Wolters Kluwer Medknow Publications, 2022)
Background: In India, newborn mortality remains high due to a number of factors, including poor quality of care at health facilities. The experience of executing complete neonatal care quality improvement (QI) package at selected hospitals in Himachal Pradesh and reduction in newborn mortality rate (NMR) is described in this study. Objective: The short-term objective was the participants' retention of knowledge and skills, and the achievement of uniform QI objectives following training and after a minimum of 6 months. Overall reduction in NMR was long-term objective. Methods: Newborn care QI package was implemented according to India Newborn Action Plan over a period of 48 months from 2013 to 2016, through infrastructure, trainings, and supportive supervision. Results: Total 13 health facilities were upgraded; 350 staff nurses and medical officers were trained. The mean posttraining knowledge score was 75% compared to 29% in the pretraining test, and 63% 1 year later. The competencies of health workers in the care of high-risk babies and 12 QI targets had improved, resulting in a 46% reduction in neonatal mortality in the state across all gestations and weights based on sample registration survey. Conclusion: Implementation of a bundle of evidence-based practices in low-resource setting for health system strengthening for intrapartum and neonatal care was linked to changed care behaviors among health-care providers, and reduction in NMR.